Acid-base balance - (:unkn) unknown (ACTA MEDICAL BELGICA, 2018)
Acid-base balance is the balance of the hydrogen ion concentrations in body fluids. The hydrogen ion (H+) concentration in body fluids is regulated within a narrow range to achieve normal metabolic and enzymatic functions as well as critical functions including fertilization, growth, protein synthesis, and cell volume regulation. Acid-base balance is under a multi-system control involving the brain, lungs, liver and kidneys. Many acid-base disorders occur due to the loss of body fluids or electrolytes from the body or their entry into the body. Electroneutrality and buffer systems are the key factors in ensuring this balance.
Keywords: acidosis; alkalosis; buffer; anion gap; HOMEOSTASIS; TRANSPORT; DISEASE